Pengembangan Media Kartu Paragraf Dengan Model Circ Untuk Keterampilan Membaca Pemahaman Peserta Didik Sekolah Dasar - Riani, Aisha Indah; Aryani, Nandita Lusiana Dewi; Kamila, Nurul Nazmi; Rahmani, Anggi (Universitas Pakuan, 2026)
DEVELOPMENT OF PARAGRAPH CARD MEDIA USING CIRC MODEL FOR READING COMPREHENSION SKILLSOF ELEMENTARY SCHOOL STUDENTSThis study aims to describe the development of paragraph card media based on the Cooperative Integrated Reading and Composition (CIRC) model to enhance fifth-grade students’ reading comprehension at SDN Nyapah 2. The study used a Research and Development (RD) approach with the ADDIE model, including Analysis, Design, Development, Implementation, and Evaluation. Data were collected through expert validation and reading comprehension tests. The developed media were interactive, visually appealing, and aligned with learning objectives. Results showed high feasibility in content and design, with students achieving an average score of 82.46 and a mastery rate of 93.10%. The media effectively guided students in identifying main ideas, understanding sentence relationships, and structuring paragraphs cooperatively.